2020
DOI: 10.1093/cid/ciaa199
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Imported Cases of Coronavirus Disease 2019 (COVID-19) in Jiangsu Province: A Multicenter Descriptive Study

Abstract: Compared with the cases in Wuhan, 80 imported cases of COVID-19 in Jiangsu Province exhibited mild or moderate symptoms and no obvious gender susceptivity, lower proportion of liver dysfunction and abnormal CT imaging and higher frequency nucleic acid detection. AbstractBackground. We aimed to report the clinical characteristics of imported coronavirus disease-19 in Jiangsu Province. Methods.We retrospectively investigated the clinical, imaging, and laboratory characteristics of confirmed cases of COVID-19 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
538
15
16

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 607 publications
(648 citation statements)
references
References 23 publications
44
538
15
16
Order By: Relevance
“…Our patients had the same other symptoms (other than ENT symptoms) as those reported in other studies [2][3][4][5][6][7]. However, just like Lechien et al, we observed that diarrhea was reported in more than 50% of patients.…”
Section: -Related Olfactory Dysfunctionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our patients had the same other symptoms (other than ENT symptoms) as those reported in other studies [2][3][4][5][6][7]. However, just like Lechien et al, we observed that diarrhea was reported in more than 50% of patients.…”
Section: -Related Olfactory Dysfunctionsupporting
confidence: 86%
“…Anosmia was never the first or second symptom to develop, but it was the third symptom in 38% (22/52) of cases. Anosmia developed 4.4 (±1.9 [1][2][3][4][5][6][7][8]) days after infection onset.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no significant association between oxygenation index and creatinine as well as uric acid among COVID-19 patients without AKI (Fig.1D-E). AKI was defined as any of renal functional indices beyond normal range 14 Note: Compared with "Mild", *P<0.05, **P<0.01, ***P<0.001; compared with "Severe", #P<0.05, ##P<0.01, ###P<0.001. a AKI was defined as any of renal functional indices beyond normal range.…”
Section: Aki Is Companied At the Early Stage Of Covid-19 Pneumoniamentioning
confidence: 99%